PENGARUH SOSIALISASI PAJAK DAN KUALITAS PELAYANAN PAJAK PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN - Amalia, Sri Wahyu; Rijal, Abdul; Hamzah, Hajrah (LPPM Universitas Bina Bangsa, 2024)
This research aims to analyze the influence of tax socialization and tax service quality in paying Land and Building Tax in Bonto Salama Village, West Sinjai District, Sinjai Regency. The population in this study was land and building tax payers in Bonto Salama Village, West Sinjai District, Sinjai Regency, consisting of 3,269 taxpayers, while the sample was 100 taxpayers taken using the purposive sampling method, the number of which was determined using the Slovin formula. Data collection was carried out using a questionnaire in the form of a questionnaire. The data analysis used is descriptive statistical analysis, instrument testing, classical assumption testing, and hypothesis testing using SPSS v. 25 for windows. The results of this research show that Tax Socialization and Tax Service Quality influence Taxpayer Compliance in paying Land and Building Tax in Bonto Salama Village, West Sinjai District, Sinjai Regency